A systematic review and meta-analysis of hepatitis E virus (HEV) in wild boars. (January 2022) - Fanelli, Angela; Tizzani, Paolo; Buonavoglia, Domenico
Abstract: This systematic review and meta-analysis summarize the available information on Hepatitis E virus (HEV) -specific antibody seroprevalence and HEV RNA prevalence in wild boar, one of the most abundant game species worldwide. A literature search (CAB Abstracts, Web of Science, Embase and Scopus) was performed to find relevant peer-reviewed works published during the period 1990–2020. A random-effect model was carried out to calculate the pooled HEV-specific antibody seroprevalence and HEV RNA prevalence estimates with 95% confidence intervals, and I 2 statistic was used to assess the heterogeneity of the data. Values by subgroups were compared according to the geographical area, age class (≤ 12 months old and > 12 months old), and sample type (bile, faeces, liver, meat/muscle, serum). Sixty-nine publications were selected, with the majority of the studies from Southern Europe ( n  = 27). The pooled HEV-specific antibody seroprevalence in wild boar was 28% (CI95% 23–34) and the HEV RNA prevalence 8% (CI95% 6–10). The analysis highlighted a significant heterogeneity among the estimates from the included studies (I 2  = 98% and I 2  = 95% for HEV-specific antibody seroprevalence and viral prevalence respectively). The moderator analysis indicated a statistically significant difference ( p -value = 0.03) for the HEV RNA prevalence according to the sample type, with the highest value in bile (17%, CI95% 9–27), followed by liver (10%, CI95% 7–14), serum (7%, CI95% 4–10), faeces (5%, CI95% 2–9), and meat/muscle (3%, CI95% 0.04–10). Finally, the HEV RNA prevalence in Europe (8.7, CI95% 6.7–11) was significantly ( p -value = 0.04) higher than in Asia (4, CI95% 0.6–8). The analysis highlights the important role of wild boar in the epidemiology of HEV. Highlights: This meta-analysis summarizes the available information on HEV infection in wild boar. The HEV pooled seroprevalence was 29% (CI95% 24–34). The HEV pooled viral prevalence was 8% (CI95% 6–10). The highest viral prevalence was found in bile (17%, CI95% 9–27), and in Europe (8.7, CI95% 6.7–11).